MENAKAR KEADILAN PUTUSAN HAKIM TERHADAP KASUS BAIQ NURIL PERSPEKTIF MAQÄSID ASY-SYARI'AH - Hanif Fudin Azhar (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2020)
This academic discourse is normative-juridical and casuistic with the integration of Islamic legal studies in the context of MaqÄá¹£id asy-Shari'ah which is aimed at the context of judicial administration by judges. This topic is examined because there is a practical ambiguity carried out by the Chief Justice in handling Baiq Nuril's legal case, namely justice which is the essence of the law in the judge's decision is not felt by Baiq Nuril. For this reason, the law produced in a judge's ruling should not only be in accordance with the laws and regulations. However, judges must also be able to examine substantively- inclusive outside normative law. In this case, the researcher uses literal- normative research methods with philosophical and normative-juridical approaches. The results of the study indicate that the judge's decision used to convict Baiq Nuril did not apply the value of legal justice which could lead to anomalies and a lack of public trust in the judiciary. Therefore, the implications of this study can lead to the context of the administration of justice by judges on the basis of legal justice.